GENERALIZATION OF MACROECONOMIC PRECONDITIONS FOR THE FORMATION OF FINANCIAL AND ECONOMIC RESULTS OF AGRICULTURAL ENTERPRISES IN THE REGION - LYZAK, Myhailo (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study focuses on the relevance of the study of macroeconomic prerequisites for the formation of financial and economic results of the management of agricultural enterprises in the region (on the example of Lviv region).The purpose of the article is the analysis and generalization of macroeconomic prerequisites for the formation of financial and economic results of agricultural enterprises of the Lviv region.The results of the analysis of the volumes of production and sale of products of agricultural enterprises of the Lviv region in 2011-2020 are presented. The structure of the production cost of products (works, services) of crop production and livestock products of agricultural enterprises of the Lviv region in 2017 and in 2020 is detailed. The volumes and dynamics of the sown areas of the main agricultural crops of the agricultural enterprises of the Lviv region in 2010, 2014-2020 were characterized. The yield indicators of the main agricultural crops of the agricultural enterprises of the Lviv region in 2010, 2014-2020 were studied.The characteristics of income, profit, financial results and profitability of agricultural enterprises of the region are provided. Conclusions have been made regarding positive aspects, as well as macroeconomic obstacles to the formation of financial and economic results of enterprises of this industry, which are implemented at the regional level. The factors that destabilize the financial and economic results of agricultural enterprises in the region include: a decrease in the sales of rye, potatoes, vegetable crops and eggs, a reduction in the sown areas of potatoes and fodder crops, the instability of the yield level and full harvest on the sown areas of certain agricultural crops, the loss of a number of enterprises, the low level of profitability and the presence of a tendency to its further decrease for open ground vegetable crops, factory sugar beet and potatoes.The applied value of the research results lies in the formation of an informational and analytical basis for the development of management decisions in terms of improving macroeconomic prerequisites for increasing the financial and economic results and performance indicators of agricultural enterprises in the region.The scientific novelty of the study consists in the improvement of the methodology of analyzing macroeconomic prerequisites for the formation of financial and economic results of agricultural enterprises in the region.
Keywords: agriculture; enterprise economy; financial and economic results; development of agriculture; macroeconomic prerequisites